Persepsi Guru Bahasa Indonesia tentang Perubahan Kurikulum - Nelvia Susmita; Agustina Agustina; Novia Juita (Departement of Mathematics Education, 2024)
This research aims to conduct a meta-analysis of several studies exploring the perceptions of Indonesian language teachers regarding curriculum changes, particularly the transition from the School Level Curriculum (KTSP) to the 2013 Curriculum and from the 2013 Curriculum to the Merdeka Curriculum. Ten studies included in this meta-analysis discuss various aspects, including teachers' perceptions, the implementation of teaching methods, challenges faced, and their impact on student learning. The analysis indicates that teachers have diverse perceptions of curriculum changes, with some feeling prepared and accepting of the changes, while others experience difficulties and confusion. The main identified challenges include limited understanding, resource constraints, high workload, and resistance to change. Nevertheless, most teachers show readiness to implement changes and consider themselves integral parts of curriculum development. The use of new teaching methods, such as the scientific approach, project-based learning, and problem-based learning, is also a focal point of the research. Despite efforts to adopt these innovative methods, some teachers face difficulties in implementing evaluations, especially in the affective and cognitive aspects. This meta-analysis illustrates the need for better training, adequate administrative support, and task redistribution for teachers to overcome the challenges of curriculum changes. Furthermore, findings suggest the necessity of a differentiated approach based on the level of education and teacher certification status